2017
DOI: 10.12669/pjms.332.11519
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of low back pain in Iranian dentists: An epidemiological study

Abstract: Objective:Low back pain (LBP) is one of the most common and prevalent work-related conditions. The aim of this study was to estimate the prevalence and risk factors associated with LBP in dentists and to analyze the association between individual and occupational characteristics and LBP.Methods:Following ethical approval, 300 dentists from Tehran Iran have voluntarily participated. Different questionnaires were completed to collect personal, occupational characteristics and the prevalence and risk factors of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
0
12
0
6
Order By: Relevance
“…Low back pain (LBP) is one of the most common and costly health problems throughout the world . About 40% of adult the population report LBP during their lifetime . Trunk stabilizer muscles such as the deep abdominal and lumbar multifidus play a major role in providing stability and preventing LBP .…”
mentioning
confidence: 99%
“…Low back pain (LBP) is one of the most common and costly health problems throughout the world . About 40% of adult the population report LBP during their lifetime . Trunk stabilizer muscles such as the deep abdominal and lumbar multifidus play a major role in providing stability and preventing LBP .…”
mentioning
confidence: 99%
“…In a study by Mohseni-Bandpei et al, the higher LBP was reported among people with the work experience more than 20 years [38]. Also, Aasa et al, reported the higher prevalence of LBP in men than women [39], while Leijon and Mulder reported a higher prevalence of LBP in women than men [40].…”
Section: Discussionmentioning
confidence: 94%
“…It is known that dentists generally work in an asymmetrical and uncomfortable position, with the head being forward and in rotation and arms being kept away from the body. 9,10 Similarly, otorhinolaryngologists also work in a position that places an excessive load on the lumbar region, especially during rhinoplasty. In studies conducted with dentists, those who worked in the same position for a long time had the most vertebral disc disorders depending on the professional working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted with dentists, those who worked in the same position for a long time had the most vertebral disc disorders depending on the professional working conditions. 9,10 However, to the best of our knowledge, there is no study in the literature investigating this issue among otorhinolaryngologists. Çınar-Medeni et al 6 observed low back pain in 70.09% of health care professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation